Mengkaji Kualitas Kimia Tanah Lahan Terlantar di Desa Tampang Kecamatan Pelaihari dan Desa Ketapang Kecamatan Bajuin Kabupaten Tanah Laut Provinsi Kalimantan Selatan - A Zainorridla; Anna Maria Makalew; Zairin Zairin (Agroekotek View, 2020)
South Kalimantan has ± 3,281,777 ha of dry land; where 67.73% is used as agricultural land, while 4.70% of the land is still abandoned. Tanah Laut Regency has ± 363,135 ha of dry land, with abandoned land at 17%. In Tampang Village in Pelaihari District and Ketapang Village in Bajuin District, there are ± 902 ha (10%) of dry land abandoned. Abandoned land can be utilized again as agricultural land if the soil quality is improved. Soil quality is determined by physical, chemical, and biological soil factors. The purpose of this study is to study the soi chemical factor in order to determine the soil quality indexes of abandoned lands in Tampang Village, Pelaihari District and Ketapang Village, Bajuin District Tanah Laut Regency South Kalimantan Province. The locations were determined through a survey using the stratified purposive sampling method. Soil sampling in each village was carried out in six locations for analyzing the characteristics of the chemical properties of the soil, namely pH, CEC, available P, organic C and total N. The study found that the soil quality index in Ketapang Village, Bajuin District was 52%, tending to be higher than in Tampang Village, Pelaihari District, which was 44%. Both of these locations have low soil quality categories because they have low pH, low available P, and low C-organic.